Endovascular treatment of occlusive central venous disease: one center's experience - Jose? Manoel da Silva Silvestre; Fernando Barbosa Trevisan; Wander Eduardo Sardinha; Domingos Moraes Filho; Eduardo Durante Ramires; Silfayner Victor Mathias Dias; Henrique Matsuda (Jornal Vascular Brasileiro, 2014)
INTRODUCTION: The majority of cases of stenosis or occlusion of central veins are the result of central catheters, arteriovenous fistulas, neoplasms or traumas and these conditions can cause severe cases of venous hypertension or reduce the flow through fistulas. The objective of this study is to analyze the results of central venous angioplasties conducted at our hospital. METHODOLOGY: We conducted a retrospective and descriptive study to analyze the results of central venous angioplasties conducted from 2010 to 2012 at a university hospital run by the Universidade Estadual de Londrina, Brazil. We calculated primary and secondary success rates and analyzed whether or not stents were used and complications occurred during a 6-month follow-up period. RESULTS: A total of 25 central venous angioplasties were conducted. Twenty-four (96%) of these were because of catheter-related intimal hyperplasia and one was to treat the effects of compression by a tumor. Fifteen (60%) angioplasties were to correct stenosis and ten (40%) were because of occlusions, with a one-hundred percent success rate for all stenosis-related procedures. However, none of the cases of occlusion could be treated endovascularly. Patency during the 6-months follow-up period was 80% after reinterventions. CONCLUSIONS: Despite good results observed after primary interventions for stenoses, it must be accepted that all current treatment options for chronic occlusive venous disease will, sooner or later, lead to restenosis or occlusion. Venous occlusions constitute a challenge demanding the development of new techniques and new materials. Prevention is paramount, through avoidance of central catheterization and early creation of arteriovenous fistulas.